THE CLINICAL EFFICACY OF ANTI-ADHESION DRUGS DURING SURGICAL TREATMENT OF TUBOOVARIAL INFERTILITY - Громова, А.М.; Нестеренко, Л.А.; Мартиненко, В.Б.; Кетова, О.М.; Талаш, В.В. (World of Medicine and Biology, 2014)
A study of the use of "Mezogel" adhesions compared with a solution to prevent adhesions during the surgical treatment of tubo-ovarial infertility women of childbearing age. Results from clinical studies have shown a significant reduction in the formation of adhesions in the postoperative period. The main criterion for the effectiveness of therapy applications "Mezogel 4%" was the pregnancy for 12 months in 66,7% of women the main group.